Early Dinner Time and Caloric Restriction Lapse Contribute to the Longevity of Nonagenarians and Centenarians of the Italian Abruzzo Region: A Cross-Sectional Study - Angelino, Donato; Pietrangeli, Francesca; Serafini, Mauro (Frontiers in Nutrition, 2022)
Recent findings showed the role of late-night eating in metabolic disorders, highlighting the importance of meal timing for health. No evidence is available on the role of meal timing for longevity. The aim of the present study was to survey, in a cross sectional study, meal timing and dietary habits of 68 nonagenarians and centenarians of the Abruzzo region, Italy. Results showed an early dinner (7.13 pm) and a calorie restriction lapse of 17.5 hours between dinner and the following lunch. Frequency of consumption was high for cereals, vegetables, fruits and legumes, low for meat, processed meat and eggs and negligible for sweets. Subjects were physically active throughout life. Our results support the importance of a daily caloric restriction lapse, hampering nocturnal postprandial stress and optimizing metabolic response, associated with a plant-based dieta high consumption of plant-based foods and physical activity for the longevity of centenarians from Abruzzo.